2012
DOI: 10.1017/s1368980011003533
|View full text |Cite
|
Sign up to set email alerts
|

Non-traditional markers of metabolic risk in prepubertal children with different levels of cardiorespiratory fitness

Abstract: Objective: To assess classical and non-classical metabolic risk biomarkers in prepubertal children with different levels of cardiorespiratory fitness (CRF). Design: CRF was assessed by the 20 m shuttle run test. To estimate physical activity, participants were observed while engaged in an after-school programme. Additionally, a short test based on a validated questionnaire was used to obtain information about physical activity practice and sedentary habits. Anthropometric parameters, blood pressure, and classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…However, Owen et al 22 , in the CHASE study, reported a strong association between PA measured objectively and CRP in a sample of Caucasian-European, Southern-Asiatic, and Afro-Caribbean children. While some studies with young subjects find negative associations between PA or cardiorespiratory fitness and CRP 2,22,23,24,25,26,27 , others do not 21,28,29,30,31,32,33,34,35,36 . Moreover, in many of these studies, the results are not presented independently from the body mass index (BMI), a potentially confounding variable of the relationship between CRP and PA or cardiorespiratory fitness 37 .…”
Section: Introductionmentioning
confidence: 96%
“…However, Owen et al 22 , in the CHASE study, reported a strong association between PA measured objectively and CRP in a sample of Caucasian-European, Southern-Asiatic, and Afro-Caribbean children. While some studies with young subjects find negative associations between PA or cardiorespiratory fitness and CRP 2,22,23,24,25,26,27 , others do not 21,28,29,30,31,32,33,34,35,36 . Moreover, in many of these studies, the results are not presented independently from the body mass index (BMI), a potentially confounding variable of the relationship between CRP and PA or cardiorespiratory fitness 37 .…”
Section: Introductionmentioning
confidence: 96%
“…It seems also that the sedentary lifestyle itself increases the risks of prematurely developing atherosclerosis and other diseases (38). One study showed that even healthy and normal weight children who were classified as having low cardiorespiratory fitness had worse metabolic and inflammatory profiles than those with better fitness (39). Longitudinal studies showed that, for obese children, physical training might improve endothelial function regardless of changes in BMI or body weight (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that cardiorespiratory fitness may have a protective effect on chronic inflammation in the paediatric population [10,11]. Similarly, some [34] but not all [35] studies in youths have shown that those with low levels of adiposity and low cardiorespiratory fitness were at greater cardiovascular risk than high-adiposity adolescents with adequate cardiorespiratory fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the paediatric population have shown an inconsistent association between cardiorespiratory fitness and inflammation independent of adiposity [11,12]. The HELENA Study conducted in ten European countries with 1025 adolescents aged 12.5e17.5 years, showed a negative association between hs-CRP and cardiorespiratory fitness; when BMI was included as a variable of adjustment, the values decreased, but still remained significant [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation